Active Fraction Combination From Liuwei Dihuang Decoction Improves Adult Hippocampal Neurogenesis and Neurogenic Microenvironment in Cranially Irradiated Mice - Wei, Mingxiao; Feng, Shufang; Zhang, Lin; Wang, Chen; Chu, Shasha; Shi, Tianyao; Zhou, Wenxia; Zhang, Yongxiang (Frontiers in Pharmacology, 2021)
Background: Cranial radiotherapy is clinically used in the treatment of brain tumours, however the consequent cognitive and emotional dysfunctions seriously impair the life quality of patients. LW-AFC, an active fraction combination extracted from classical traditional Chinese medicine prescription Liuwei Dihuang decoction, can improve cognitive and emotional dysfunctions in many animal models, however the protective effect of LW-AFC on cranial irradiation-induced cognitive and emotional dysfunctions has not been reported. Recent studies indicate that impairment of adult hippocampal neurogenesis (AHN) and alterations of neurogenic microenvironment in hippocampus constitute critical factors in cognitive and emotional dysfunctions following cranial irradiation. Here, our research further investigated the potential protective effects and mechanisms of LW-AFC on cranial irradiation-induced cognitive and emotional dysfunctions in mice. Methods: LW-AFC (1.6 g/kg) was intragastrically administered to mice for 14 days before cranial irradiation (7 Gy γ-ray). AHN was examined by quantifying the number of proliferative neural stem cells and immature neurons in dorsal and ventral hippocampus. The contextual fear conditioning test, open field test, and tail suspension test were used to assess cognitive and emotional functions in mice. To detect the change of neurogenic microenvironment, colorimetry and multiplex bead analysis were performed to measure the level of oxidative stress, neurotrophic and growth factors, and inflammation in hippocampus. Results: LW-AFC exerted beneficial effects on the contextual fear memory, anxiety behaviour, and depression behaviour in irradiated mice. Moreover, LW-AFC increased the number of proliferative neural stem cells and immature neurons in dorsal hippocampus, displaying a regional specificity of neurogenic response. For neurogenic microenvironment, LW-AFC significantly increased the contents of SOD, GSH-Px, GSH, and CAT, and decreased the content of MDA in hippocampus of irradiated mice, accompanied by the increase of BDNF, IGF-1, and IL-4 contents. Together, LW-AFC improved cognitive and emotional dysfunctions, promoted AHN preferentially in dorsal hippocampus, and ameliorated disturbance of neurogenic microenvironment in irradiated mice. Conclusion: LW-AFC ameliorates cranial irradiation-induced cognitive and emotional dysfunctions, and the underlying mechanisms are mediated by promoting AHN in dorsal hippocampus and improving neurogenic microenvironment. LW-AFC might be a promising therapeutic agent to treat cognitive and emotional dysfunctions in patients receiving cranial radiotherapy.